Pengembangan Aplikasi Perangkat Mobile Sebagai Pengirim Data Dari Lapangan Menuju Pusat Data Menggunakan Algoritme Flooding - Fauzan Pahlawan; Adhitya Bhawiyuga; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Internet of Things (IoT) is a network of things which able communicate about surrounding information with other things by using simple computer, communication device, and censor without the need of human interaction. Generally the data in the network will be collected to a main computer which will be processed and send to the data centre using internet connection. However in the case where there is no internet infrastructure the data cannot be send to data centre. Hence the development of mobile application which can be used to gather and bring the data to area with internet infrastructure and send it to the data centre. To help the process of the data delivery the developed application has a feature to be able to send data to other mobile device without using internet connection using WiFi-Direct. To handle multiple data transmission, in the case the courier of the data meet more than once device, the developed application also implement flooding algorithm where the data will only be sent to the directly connected adjacent which suitable with the WiFi-Direct constraint that is not able to form multi-hop connection. The development of the application is completed using object oriented approach through analysis, design, and implementaion stage. The mobile application has been successfully developed and is able to fulfill all the required functions to solve the problem of sending the data from the field to data centre based on the 100% validation test result from the black box testing. With tested performance of maximum connection range, optimal connection range, total time required to form a connection between mobile application and total time required to send data between mobile application.